Peran Sumber Daya Sosial Budaya dalam Pengembangan Pariwisata di Kawasan Gunung Merapi Desa Umbulharjo dan Desa Kepuharjo - Shafira Leliana Putri; Maya Damayanti (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2017)
Community is one of the main elements of development, so that all forms of development will involve community both as subjects and objects. Socio-cultural resources are inherent in society, accordingly when society develops a business, directly or indirectly, consciously or unconsciously, people have been using socio-cultural resources. There are tourist attractions that has long been recognized by domestic and foreign tourists in disaster-prone areas of Mount Merapi, in Umbulharjo and Kepuharjo village, Sleman, D.I.Y. There are special interest tourism such as tourist villages, national park, and post-disaster area. Although not a cultural tourism, the slopes of Mount Merapi inhabited by people who uphold the Javanese socio-cultural values. Perception, behavior, policies applied in tourism activities are influenced by the culture. Hence, what are the roles of socio-cultural resources for tourism development in Merapi Mount area? By knowing roles of socio-cultural resources in tourism development, hopefully stakeholders can make the best use of socio-cultural resources at the same time preserving it. Qualitative method used in this study, data collected by observation and depth interviews with 13 vocal figure in Umbulharjo and Kepuharjo Village. By using thematic descriptive analysis, researchers identified socio-cultural resources in each tourism activities. This research found 5 roles of socio-cultural resources in this tourism development, they are as branding, attractions, rules, institutional and development catalyst.